Fundamental Frequency Decomposition of Slender Structures on a Self-Tandem Dual Satellite - Jiang, Guowei; Lin, Baojun; Li, Kai; Yang, Jiayue; Zhao, Ying; Liu, Jiawei (Frontiers in Mechanical Engineering, 2022)
In order to make full use of the carrying capacity of rocket and reduce the invalid mass of satellite, the first-order fundamental frequency of self-tandem dual satellite should be effectively decomposed into the designed fundamental frequency of each satellite. In this paper, the fundamental frequency of self-tandem dual satellite is analyzed based on the beam theory of slender structure arranged in tandem and Rayleigh-Ritz theory. The influence of stiffness ratio, mass ratio and size ratio on the first-order fundamental frequency of the dual satellite is also discussed. Based on the results, the decomposition method of the first-order fundamental frequency index of the self-tandem dual satellite is proposed, taking into consideration of the influence of manufacturing error and the joint stiffness between satellites. The numerical simulation is verified against experiments, setting the dual satellite on the same platform and on different platforms. The results show that the decomposition method can effectively decompose the first-order fundamental frequency of self-tandem dual satellite. The result is within the required error range and the error is less than 6.5%. The calculation can effectively improve the specific stiffness and functional density of the satellite, reducing the overall development risk.